Fluorine Triggered Surface and Lattice Regulation in Anatase TiO2−xFx Nanocrystals for Ultrafast Pseudocapacitive Sodium Storage. Issue 50 (23rd November 2020) - Ni, Mingzhu; Sun, Da; Zhu, Xiaohui; Xia, Qiuying; Zhao, Yang; Xue, Liang; Wu, Jianghua; Qiu, Ce; Guo, Qiubo; Shi, Zhengyi; Liu, Xiaojing; Wang, Gongming; et al.
Abstract: Sodium‐ion batteries (SIBs) have been considered as one of the most promising secondary battery techniques for large‐scale energy storage applications. However, developing appropriate electrode materials that can satisfy the demands of long‐term cycling and high energy/power capabilities remains a challenge. Herein, a fluorine modulation strategy is reported that can trigger highly active exposed crystal facets in anatase TiO2− x F x, while simultaneously inducing improved electron transfer and Na + diffusion via lattice regulation. When tested in SIBs, the optimized fluorine doped TiO2− x F x nanocrystals exhibit a high reversible capacity of 275 mA h g −1 at 0.05 A g −1, outstanding rate capability (delivering 129 mA h g −1 at 10 A g −1 ), and remarkable cycling stability with 91% capacity retained after 6000 cycles at 2 A g −1 . Importantly, the optimized TiO2− x F x nanocrystals are dominated by pseudocapacitive Na + storage, which can be attributed to the fluorine induced surface and lattice regulation, enabling ultrafast electrode kinetics. Abstract : Fluorine triggered surface and lattice regulation are simultaneously realized in anatase TiO2− x F x nanocrystals, which induce improved electron transfer, affluent active exposed crystal facets, and enlarged diffusion channels for efficient faradaic reaction with fast Na + insertion/extraction. With greatly improved electrode kinetics, the optimized TiO2− x F x nanocrystals enable ultrastable and ultrafast pseudocapacitive Na + storage in the electrode.